Exploiting Urazole’s Acidity for Fabrication of Hydrogels and Ion-Exchange Materials - Saltuk B. Hanay; Ali Fallah; Efsun Senturk; Zeliha Yetim; Ferdows Afghah; Hulya Yilmaz; Mustafa Culha; Bahattin Koc; Ali Zarrabi; Rajender S. Varma (Gels, 2021)
In this study, the acidity of urazole (pKa 5–6) was exploited to fabricate a hydrogel in two simple and scalable steps. Commercially available poly(hexamethylene)diisocyanate was used as a precursor to synthesize an urazole containing gel. The formation of urazole was confirmed by FT-IR and 1H-NMR spectroscopy. The hydrogel was characterized by microscopy imaging as well as spectroscopic and thermo-gravimetric analyses. Mechanical analysis and cell viability tests were performed for its initial biocompatibility evaluation. The prepared hydrogel is a highly porous hydrogel with a Young’s modulus of 0.91 MPa, has a swelling ratio of 87%, and is capable of exchanging ions in a medium. Finally, a general strategy was demonstrated to embed urazole groups directly into a crosslinked material.